Prednisona e meloxicam no tratamento de ratos submetidos ao trauma agudo da medula espinhal - Aiello, Graciane (2012)
Considering the relevance of study of traumatic spinal cord injury in humans and animals, the aim of the study was investigated the use of the prednisone and meloxicam in treatment of rats submitted the experimental model of acute spinal cord injury with 2Fr Fogarty catheter with evaluation of oxidative stress, Neurological tests and histological exam. Ninety rats were divided in six groups: GCS or saline (n=15), GCP or prednisone control (n=15), GCM or meloxicam control, GTS or trauma saline (n=15), GTP or trauma meloxicam (n=15) and GTM or trauma prednisone (n=15). Each group was divided into three subgroups according to treatment time in the postoperative period of 24h, 72h and seven days. All groups were submitted laminectomy and in the groups GTS, GTM and GTP, after exposure of the spinal cord was performed compressive spinal cord injury with 2Fr Fogarty catheter. The GCS and GTS was treated with saline (0,5ml/rat/day), GSM and GTM with meloxicam (2mg/kg/day) and GSP and GTP with prednisone (2mg/kg/dia). Neurological tests were performed (BBB, inclined plane and deep pain) 24 hours before and after surgery and repeated every 48 hours until the day of euthanasia. The parameters of oxidative stress were evaluated and performed histopathological analysis of the spinal cord. The groups GTS, GTM and GTP in the different times were no point in the BBB scale and three points in the inclined plane and absence of deep pain. GTM and GTS groups had lower catalase activity and TBARS levels when compared to the GTS and they were more evident to 72 hours postoperative period, indicating a possible antioxidant effect. In the GTS group, there was persistence of this action until the seventh day after trauma. In the histopathological exam were found Wallerian degeneration and necrosis of gray matter of intensity variation, with no significant difference between undergone to trauma. Meloxicam and prednisone can have neuroprotective and antioxidant effect, but the necrosis and Wallerian degeneration were not stop in rats submitted the acute spinal cord injury with 2Fr Fogarty catheter.